A method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating

Through magnetron sputtering copper plating technology and plasma activation treatment, the problem of insufficient conductivity and surface uniformity of the negative electrode current collector copper foil of lithium-ion battery is solved, and higher conductivity and adhesion are achieved, reducing wear resistance .

CN118639205BActive Publication Date: 2025-02-11DONGGUAN HUICHENG VACUUM TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411001377.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-02-11
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The negative electrode current collector copper foil of lithium-ion batteries is difficult to maintain good conductivity and surface uniformity in the battery, affecting the electrochemical performance.

Method used

Magneto-controlled sputtering copper plating technology is used to coat the upper and lower surfaces of the copper foil of lithium battery electrode with a preset thickness, and the surface characteristics are further optimized through plasma activation treatment and chemical plating.

Benefits of technology

The conductive properties and surface uniformity of the copper foil are improved, the adhesion to other materials is improved, the conductivity is enhanced, and the wear resistance is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118639205B_ABST
    Figure CN118639205B_ABST
Patent Text Reader

Abstract

The invention discloses a method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating, and relates to the technical field of lithium battery material manufacturing. The method comprises: cutting a copper foil to be treated in a clean room; wherein the copper foil is an electrolytic copper foil or a very low profile copper foil; placing the cut copper foil in a plasma reaction chamber, and performing plasma activation treatment on the surface of the cut copper foil; under the preset process conditions, using magnetron sputtering copper plating to plate a thin film copper layer of preset thickness on both the upper and lower surfaces of the lithium battery electrode copper foil; chemically electroplating the lithium battery electrode copper foil plated with the thin film copper layer, and electroplating the thickness of the thin film copper layer on both sides of the lithium battery electrode copper foil to 1 micron. The invention improves the characteristics of the copper foil as a lithium ion battery material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery material manufacturing, and in particular to a method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating. Background Art

[0002] Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, separators and electrolytes. When charging, the potential applied to the two poles of the battery forces the lithium-intercalated compounds in the positive electrode to release lithium ions, which are then embedded in the hexagonal graphite negative electrode after passing through the separator; when discharging, lithium ions are precipitated from the graphite in the sheet structure and recombined with the lithium-intercalated compounds in the positive electrode. The movement of lithium ions generates current. Although the structure of lithium-ion batteries and the chemical reaction principles of the charging and discharging process are very simple, many issues need to be considered in actual commercial applications. For example, the conductivity of the positive and negative electrode materials, the charge and discharge potential, activity, the structural stability of lithium intercalation, rate performance and safety performance, as well as the stability, conductivity and environmental adaptability of the electrolyte.

[0003] Lithium batteries use copper foil as the negative electrode current collector of lithium-ion batteries. Copper foil acts as both a carrier of negative electrode active materials and a collector and transmitter of negative electrode electron flow in the battery. Therefore, the copper foil current collector has a great influence on the electrochemical performance of lithium-ion batteries, that is, it must have good electrical conductivity and the surface can be evenly coated with negative electrode materials without falling off.

[0004] Therefore, it is very meaningful to propose a method of improving the performance of lithium battery electrodes by using magnetron sputtering copper plating. Summary of the invention

[0005] The embodiment of the present invention provides a method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating to solve the above technical problems.

[0006] The present invention provides a method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating, comprising:

[0007] Cutting the copper foil to be processed in a clean room; wherein the copper foil is electrolytic copper foil or very low profile copper foil;

[0008] Placing the cut copper foil in a plasma reaction chamber, and performing plasma activation treatment on the surface of the cut copper foil; wherein the plasma activation treatment on the surface of the cut copper foil comprises: generating plasma by applying a high-frequency electric field in the plasma reaction chamber; the generated plasma interacts with the surface of the cut copper foil, causing the atoms and molecules on the surface of the cut copper foil to recombine and dissociate;

[0009] Fixing the copper foil after the plasma activation treatment on the unwinding roller position of the vacuum magnetron sputtering coating equipment;

[0010] The vacuum magnetron sputtering coating equipment is adjusted to preset process conditions; wherein the preset process conditions include: the coating speed is set in the range of 0.2 to 5 meters per minute, the coating temperature is set in the range of 80 to 200 degrees Celsius; the process pressure is set in the range of 0.1 to 0.7 Pa, the ion source power is set in the range of 0.1 to 5 kilowatts, the DC magnetron sputtering cathode power is set in the range of 0.3 to 30 kilowatts, and the vacuum degree is set to be higher than 0.002 Pa;

[0011] Under the preset process conditions, a thin film copper layer of a preset thickness is plated on both the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating;

[0012] The lithium battery electrode copper foil plated with the thin film copper layer is subjected to chemical electroplating, and the thickness of the thin film copper layer on both sides of the lithium battery electrode copper foil is electroplated to 1 micron.

[0013] Furthermore, in the process of plating a thin film copper layer of a preset thickness on both the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating, the method further comprises:

[0014] Acquire an image of the upper surface of the lithium battery electrode copper foil, an image of the lower surface of the lithium battery electrode copper foil, and an image of the lithium battery electrode copper foil in a thickness direction after the lithium battery electrode copper foil has been magnetron sputtered for a first preset time;

[0015] Determine the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for the first preset time based on the image of the upper surface of the lithium battery electrode copper foil, the image of the lower surface of the lithium battery electrode copper foil, and the image of the lithium battery electrode copper foil in the thickness direction;

[0016] If the real-time surface flatness is within the preset flatness range, the magnetron sputtering copper plating process of the thin film copper layer is terminated.

[0017] Furthermore, based on the image of the upper surface of the lithium battery electrode copper foil, the image of the lower surface of the lithium battery electrode copper foil, and the image of the lithium battery electrode copper foil in the thickness direction, determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time includes:

[0018] Converting the image of the upper surface of the lithium battery electrode copper foil into a first grayscale image, and performing bit layering on the first grayscale image to obtain a first bit layered image;

[0019] Converting the image of the upper surface of the lithium battery electrode copper foil into a second grayscale image, and performing bit layering on the second grayscale image to obtain a second bit layered image;

[0020] Determining a grayscale difference value of each image block in the first bit layered image;

[0021] Determining a grayscale difference value of each image block in the second bit layered image;

[0022] Taking the image in the thickness direction of the lithium battery electrode copper foil as a reference, based on the grayscale difference value of each image block in the first bit layered image and the grayscale difference value of each image block in the second bit layered image, determine the first concave-convex point on the upper surface of the lithium battery electrode copper foil and the second concave-convex point on the lower surface of the lithium battery electrode copper foil; wherein the concave-convex coefficient corresponding to the first concave-convex point exceeds the preset concave-convex reference value, and the concave-convex coefficient corresponding to the second concave-convex point exceeds the preset concave-convex reference value;

[0023] The real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for the first preset time is determined according to the number and position of the first concave-convex points and the number and position of the second concave-convex points.

[0024] Furthermore, the grayscale difference value of each image block in the first bit layered image is calculated based on the following formula;

[0025]

[0026] in, is the grayscale difference value of the i-th image block in the first bit layered image; represents the grayscale difference value of the pixel at the jth position in the ith image block in the first bit layered image; m represents the number of rows of the image block; and n represents the number of columns of the image block.

[0027] Furthermore, the grayscale difference value of each image block in the second bit layered image is calculated based on the following formula;

[0028]

[0029] in, is the grayscale difference value of the i-th image block in the second bit layered image; represents the grayscale difference value of the pixel at the jth position in the ith image block in the second bit layered image; m represents the number of rows of the image block; and n represents the number of columns of the image block.

[0030] Furthermore, after determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time, the method further includes:

[0031] If the real-time surface flatness is not within the preset flatness range, the magnetron sputtering copper plating process of the thin film copper layer is continued.

[0032] Furthermore, before chemically electroplating the lithium battery electrode copper foil plated with the thin film copper layer, the method further comprises:

[0033] The lithium battery electrode copper foil plated with the thin film copper layer is subjected to heating annealing treatment under a vacuum state to eliminate the metal stress inside the lithium battery electrode copper foil plated with the thin film copper layer.

[0034] Furthermore, the temperature during the heating annealing treatment is set in the range of 80 to 180 degrees Celsius.

[0035] Furthermore, the preset thickness is 10 to 20 nanometers.

[0036] Furthermore, the size of the copper foil after cutting is 0.1 to 0.9 meters.

[0037] Based on the content of the invention provided by the present invention, the copper foil to be treated is cut in a clean room, the cut copper foil is placed in a plasma reaction chamber, and the surface of the cut copper foil is subjected to plasma activation treatment; under preset process conditions, a thin film copper layer of preset thickness is plated on the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating; the lithium battery electrode copper foil plated with the thin film copper layer is chemically electroplated, and the thickness of the thin film copper layer on both sides of the lithium battery electrode copper foil is electroplated to 1 micron. In other words, the copper foil is placed in a plasma reaction chamber, and the surface of the copper foil is subjected to plasma activation treatment. The recombination and dissociation reactions can lead to physical and chemical changes on the surface of the copper foil, that is, the surface activity of the copper foil can be improved, the surface roughness of the copper foil can be increased, and the chemical reaction activity of the surface of the copper foil can be increased, so that the following technical effects can be further achieved: improving the characteristics of the copper foil as a lithium ion battery material, improving the adhesion of the copper foil to other materials, increasing the conductivity of the copper foil, and reducing the wear resistance of the copper foil. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The drawings described herein are used to provide a further understanding of the embodiments of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0039] Figure 1 A flowchart of an optional method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating according to an embodiment of the present invention;

[0040] Figure 2 The present invention is a flowchart of another optional method for improving the performance of lithium battery electrodes by copper plating using magnetron sputtering according to an embodiment of the present invention.

[0041] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0042] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0043] Alternatively, if Figure 1 As shown, the present invention provides a method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating, comprising:

[0044] S101, cutting the copper foil to be processed in a clean room; wherein the copper foil is electrolytic copper foil or very low profile copper foil;

[0045] S102, placing the cut copper foil in a plasma reaction chamber, and performing plasma activation treatment on the surface of the cut copper foil; wherein the plasma activation treatment on the surface of the cut copper foil includes: generating plasma by applying a high-frequency electric field in the plasma reaction chamber; the generated plasma interacts with the surface of the cut copper foil, causing the atoms and molecules on the surface of the cut copper foil to recombine and dissociate;

[0046] S103, fixing the copper foil after the plasma activation treatment on the unwinding roller position of the vacuum magnetron sputtering coating equipment;

[0047] S104, adjusting the vacuum magnetron sputtering coating equipment to a preset process condition; under the preset process condition, using a magnetron sputtering copper plating method to plate a thin film copper layer of a preset thickness on both the upper and lower surfaces of the lithium battery electrode copper foil;

[0048] S105, chemically electroplating the lithium battery electrode copper foil plated with the thin film copper layer, and electroplating the thin film copper layer on both sides of the lithium battery electrode copper foil to a thickness of 1 micron.

[0049] In some embodiments of the present invention, the preset process conditions include: the coating speed is set in the range of 0.2 to 5 meters per minute, the coating temperature is set in the range of 80 to 200 degrees Celsius; the process pressure is set in the range of 0.1 to 0.7 Pa, the ion source power is set in the range of 0.1 to 5 kilowatts, the DC magnetron sputtering cathode power is set in the range of 0.3 to 30 kilowatts, and the vacuum degree is set to be higher than 0.002 Pa;

[0050] Based on the embodiment provided by the present invention, the copper foil to be treated is cut in a clean room, the cut copper foil is placed in a plasma reaction chamber, and the surface of the cut copper foil is subjected to plasma activation treatment; under preset process conditions, a thin film copper layer of preset thickness is plated on the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating; the lithium battery electrode copper foil plated with the thin film copper layer is chemically electroplated, and the thickness of the thin film copper layer on both sides of the lithium battery electrode copper foil is electroplated to 1 micron. In other words, the copper foil is placed in a plasma reaction chamber, and the surface of the copper foil is subjected to plasma activation treatment. The recombination and dissociation reactions can lead to physical and chemical changes on the surface of the copper foil, which can improve the surface activity of the copper foil, increase the surface roughness of the copper foil, and increase the chemical reaction activity of the surface of the copper foil, so as to achieve the following technical effects: improve the characteristics of the copper foil as a lithium ion battery material, improve the adhesion of the copper foil to other materials, increase the conductivity of the copper foil, and reduce the wear resistance of the copper foil.

[0051] Furthermore, in the process of plating a thin film copper layer of a preset thickness on both the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating, the method further includes:

[0052] Acquire an image of the upper surface of the lithium battery electrode copper foil, an image of the lower surface of the lithium battery electrode copper foil, and an image of the lithium battery electrode copper foil in a thickness direction after the lithium battery electrode copper foil has been magnetron sputtered for a first preset time;

[0053] Determine the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time based on the image of the upper surface of the lithium battery electrode copper foil, the image of the lower surface of the lithium battery electrode copper foil, and the image of the lithium battery electrode copper foil in the thickness direction;

[0054] If the real-time surface flatness is within the preset flatness range, the magnetron sputtering copper plating process of the thin film copper layer is terminated.

[0055] Based on the embodiments provided by the present invention, monitoring the real-time surface flatness is beneficial to improving the flatness of the film layer obtained after the magnetron sputtering process, thereby improving the performance of the lithium battery electrode.

[0056] Furthermore, if Figure 2 As shown, based on the image of the upper surface of the lithium battery electrode copper foil, the image of the lower surface of the lithium battery electrode copper foil, and the image of the lithium battery electrode copper foil in the thickness direction, the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time is determined, including:

[0057] S201, converting an image of the upper surface of the copper foil of the lithium battery electrode into a first grayscale image, and performing bit layering on the first grayscale image to obtain a first bit layered image;

[0058] S202, converting the image of the upper surface of the copper foil of the lithium battery electrode into a second grayscale image, and performing bit layering on the second grayscale image to obtain a second bit layered image;

[0059] S203, determining the grayscale difference value of each image block in the first bit layered image; determining the grayscale difference value of each image block in the second bit layered image;

[0060] S204, taking the image in the thickness direction of the lithium battery electrode copper foil as a reference, based on the grayscale difference value of each image block in the first bit layered image and the grayscale difference value of each image block in the second bit layered image, determining the first concave-convex point on the upper surface of the lithium battery electrode copper foil and the second concave-convex point on the lower surface of the lithium battery electrode copper foil; wherein the concave-convex coefficient corresponding to the first concave-convex point exceeds the preset concave-convex reference value, and the concave-convex coefficient corresponding to the second concave-convex point exceeds the preset concave-convex reference value;

[0061] S205, determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time according to the number and position of the first concave-convex points and the number and position of the second concave-convex points.

[0062] Further, the grayscale difference value of each image block in the first bit layered image is calculated based on the following formula;

[0063]

[0064] in, is the grayscale difference value of the i-th image block in the first bit layered image; It represents the grayscale difference value of the pixel at the jth position in the ith image block in the first bit layered image; m represents the number of rows of the image block; and n represents the number of columns of the image block.

[0065] Further, the grayscale difference value of each image block in the second bit layered image is calculated based on the following formula;

[0066]

[0067] in, is the grayscale difference value of the i-th image block in the second bit layered image; It represents the grayscale difference value of the pixel at the jth position in the ith image block in the second bit layered image; m represents the number of rows of the image block; and n represents the number of columns of the image block.

[0068] Further, after determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time, the method further includes:

[0069] If the real-time surface flatness is not within the preset flatness range, the magnetron sputtering copper plating process of the thin film copper layer is continued.

[0070] Furthermore, before chemically electroplating the lithium battery electrode copper foil plated with the thin film copper layer, the method further comprises:

[0071] The lithium battery electrode copper foil coated with a thin film copper layer is subjected to heating annealing treatment under a vacuum state to eliminate the metal stress inside the lithium battery electrode copper foil coated with the thin film copper layer.

[0072] According to the embodiment provided by the present invention, after an aluminum film is deposited on the surface of the copper foil, an annealing treatment is performed under a vacuum state to eliminate the metal stress inside the copper foil, thereby improving the mechanical properties of the copper foil.

[0073] Furthermore, the temperature during the heating annealing treatment is set in the range of 80 to 180 degrees Celsius.

[0074] Furthermore, the preset thickness is 10 to 20 nanometers.

[0075] Furthermore, the size of the copper foil after cutting is 0.1 to 0.9 meters.

[0076] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for improving the performance of lithium battery electrodes by magnetron sputtering copper plating, characterized in that: include: Cutting the copper foil to be processed in a clean room; wherein the copper foil is electrolytic copper foil or very low profile copper foil; Placing the cut copper foil in a plasma reaction chamber, and performing plasma activation treatment on the surface of the cut copper foil; wherein the plasma activation treatment on the surface of the cut copper foil comprises: generating plasma by applying a high-frequency electric field in the plasma reaction chamber; the generated plasma interacts with the surface of the cut copper foil, causing the atoms and molecules on the surface of the cut copper foil to recombine and dissociate; Fixing the copper foil after the plasma activation treatment on the unwinding roller position of the vacuum magnetron sputtering coating equipment; The vacuum magnetron sputtering coating equipment is adjusted to preset process conditions; wherein the preset process conditions include: the coating speed is set in the range of 0.2 to 5 meters per minute, the coating temperature is set in the range of 80 to 200 degrees Celsius; the process pressure is set in the range of 0.1 to 0.7 Pa, the ion source power is set in the range of 0.1 to 5 kilowatts, the DC magnetron sputtering cathode power is set in the range of 0.3 to 30 kilowatts, and the vacuum degree is set to be higher than 0.002 Pa; Under the preset process conditions, a thin film copper layer of preset thickness is plated on both the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating; Chemically electroplating the lithium battery electrode copper foil plated with the thin film copper layer, electroplating the thin film copper layer on both sides of the lithium battery electrode copper foil to a thickness of 1 micron; In the process of plating a thin film copper layer of a preset thickness on both the upper and lower surfaces of the lithium battery electrode copper foil by magnetron sputtering copper plating, the method further comprises: Acquire an image of the upper surface of the lithium battery electrode copper foil, an image of the lower surface of the lithium battery electrode copper foil, and an image of the lithium battery electrode copper foil in a thickness direction after the lithium battery electrode copper foil has been magnetron sputtered for a first preset time; Determine the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for the first preset time based on the image of the upper surface of the lithium battery electrode copper foil, the image of the lower surface of the lithium battery electrode copper foil, and the image of the lithium battery electrode copper foil in the thickness direction; If the real-time surface flatness is within a preset flatness range, the magnetron sputtering copper plating process of the thin film copper layer is terminated; Based on the image of the upper surface of the lithium battery electrode copper foil, the image of the lower surface of the lithium battery electrode copper foil, and the image of the lithium battery electrode copper foil in the thickness direction, determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time, including: Converting the image of the upper surface of the lithium battery electrode copper foil into a first grayscale image, and performing bit layering on the first grayscale image to obtain a first bit layered image; Converting the image of the upper surface of the lithium battery electrode copper foil into a second grayscale image, and performing bit layering on the second grayscale image to obtain a second bit layered image; Determining a grayscale difference value of each image block in the first bit layered image; Determining a grayscale difference value of each image block in the second bit layered image; Taking the image in the thickness direction of the lithium battery electrode copper foil as a reference, based on the grayscale difference value of each image block in the first bit layered image and the grayscale difference value of each image block in the second bit layered image, determine the first concave-convex point on the upper surface of the lithium battery electrode copper foil and the second concave-convex point on the lower surface of the lithium battery electrode copper foil; wherein the concave-convex coefficient corresponding to the first concave-convex point exceeds the preset concave-convex reference value, and the concave-convex coefficient corresponding to the second concave-convex point exceeds the preset concave-convex reference value; Determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for the first preset time according to the number and position of the first concave-convex points and the number and position of the second concave-convex points; Calculate the grayscale difference value of each image block in the first bit layered image based on the following formula; in, is the grayscale difference value of the i-th image block in the first bit layered image; represents the grayscale difference value of the pixel at the jth position in the ith image block in the first bit layered image; m represents the number of rows of the image block; n represents the number of columns of the image block; Calculating the grayscale difference value of each image block in the second bit layered image based on the following formula; in, is the grayscale difference value of the i-th image block in the second bit layered image; represents the grayscale difference value of the pixel at the jth position in the i-th image block in the second bit layered image; m represents the number of rows of the image block; n represents the number of columns of the image block; after determining the real-time surface flatness of the lithium battery electrode copper foil after magnetron sputtering for a first preset time, the method further includes: If the real-time surface flatness is not within the preset flatness range, the magnetron sputtering copper plating process of the thin film copper layer is continued.

2. The method for improving the performance of lithium battery electrodes by magnetron sputtering copper plating according to claim 1, characterized in that: Before chemically electroplating the lithium battery electrode copper foil plated with the thin film copper layer, the method further comprises: The lithium battery electrode copper foil plated with the thin film copper layer is subjected to heating annealing treatment under a vacuum state to eliminate the metal stress inside the lithium battery electrode copper foil plated with the thin film copper layer.

3. The method for improving the performance of lithium battery electrodes by magnetron sputtering copper plating according to claim 2, characterized in that: The temperature during the heating annealing process is set within a range of 80 to 180 degrees Celsius.

4. The method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating according to claim 1, characterized in that: The preset thickness is 10 to 20 nanometers.

5. The method for improving the performance of lithium battery electrodes by using magnetron sputtering copper plating according to claim 1, characterized in that: The size of the copper foil after cutting is 0.1 to 0.9 meters.

Citation Information

Patent Citations

  • Method for improving electrical performance of positive electrode collector electrode of lithium battery

    CN106435494A

  • Method for eliminating light transmission points of composite copper foil

    CN117265530A